Penerapan Siklus Plan-Do-Check-Act (PDCA) untuk Mengurangi Pemborosan dalam Industri Jasa - Rahmayanti, Dina; Wirdianto, Eri; Afrileni, Wirna (Universitas Teuku Umar, 2025)
This research aims to increase the efficiency of aging time in the car refurbished process in T XYZ by applying the PDCA (Plan-Do-Check-Action) method. The company's main problem is the high number of idle cars due to aging times that exceed standards, especially in repair, service, and preparation activities. The research methods used include identifying the root of the problem using a fishbone diagram, designing solutions using the 5W+1H approach, improving implementation, and evaluating results. Implementation results show a decrease in the average aging time: in repair from 5,333 to 3,833 days, in service from 6 to 3,333 days, and preparation from 1,333 to 0.967 days. The number of idle cars also decreased gradually to reach 86 units with an actual aging time of one day. These findings prove that implementing PDCA effectively increases the efficiency of the refurbished process, reduces time waste, and supports increased company operational performance. This research contributes to developing continuous improvement practices in the automotive industry. It can be a reference for other service companies that are optimizing productivity through a quality management approach.